Prevalence and pattern of multimorbidity in China: a cross-sectional study of 224,142 adults over 60 years old - Hu, Xing; Li, Shugang; Wei, Zhimin; Wu, Dishan; Meng, Lingbing; Li, Jianyi; Xu, Jiapei; Zhang, Luyao; Ma, Qinan; Li, Hui; Zeng, Xuezhai; Zhang, Qiuxia; et al. (Frontiers in Public Health, 2024)
Aim To examine the prevalence and potential risk factors of multimorbidity among older adult in China. In addition, we investigated the pattern of multimorbidity. Methods This study is based on data from the fourth Sample Survey of the Aged Population in Urban and Rural China (SSAPUR) in 2015, a comprehensive survey of individuals aged 60 years or older in China. We calculated baseline data and prevalence rates for comorbidities, stratified by household registration, age, sex, education, exercise, and health insurance. Univariate and multivariate logistic regression analyses were conducted to identify potential risk factors for comorbidities. Furthermore, we determined the prevalence rates for the three most frequent disease combinations. Results A total of 215,040 participants were included in our analysis. The prevalence of multimorbidity was 50.5% among the older adult in China. The prevalence rate was slightly higher in rural areas than in urban areas, with rates of 51.5 and 49.6%, respectively (p < 0.001). Moreover, the prevalence rate was higher in females than in males, with rates of 55.2 and 45.3%, respectively (p < 0.001). Multivariate logistic regression analysis revealed that individuals aged 70–79 years (OR:1.40, 95% CI: 1.38–1.43, p < 0.001) and over 80 years (OR:1.41, 95% CI: 1.38–1.45, p < 0.001) had a higher prevalence of multimorbidity than those aged 60–69 years. The most prevalent pair of comorbidities was hypertension and osteoarthropathy, with 19.6% of the participants having these two conditions, accounting for 5.4% of the total participants. Conclusion Our findings indicate a high prevalence of multimorbidity among the older adult in China. Increased expenditure on preventive health care, popularization of general medicine and popular medical education may be adopted by the Government to cope with the high prevalence of multimorbidity.